PENGARUH PROPORSI KOMISARIS INDEPENDEN, KINERJA LINGKUNGAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENGUNGKAPAN LINGKUNGAN - I Made Juniartha; Raden Rosiyana Dewi (Jurnal Akuntansi Trisakti, 2017)
The research was conducted aimed at finding empirical evidence on the influence of the proportion of independent commissioners, environmental performance and company growth on corporate environmental disclosures. This study uses a sample of all companies listed on the IDX during 2014 - 2016. The total sample that meets the criteria is 25 companies. The data source used is an annual report, collected using the purposive sampling method. Testing the hypothesis by using multiple regression with the panel method. The results of this study state that the variable proportion of independent commissioners and environmental performance has a positive effect on environmental disclosure, and the proportion of public ownership as a moderation of the relationship of independent commissioners with environmental disclosures and the relationship of environmental performance with environmental disclosure.